The Harmony of Symbols - Whittle, Alasdair (Oxbow Books, 1999)
Three circuits of ditches comprise the Windmill Hill enclosure, which was re-examined in 1988 as part of wider research into the area's Neolithic sequence and environment, and the context in which monuments were built, used and abandoned. Detailed results are set out by category and theme, and abundant environmental evidence is presented covering soils, land snails, plant remains, charcoals, pollen, amphibian and small mammal remains. This volume advances many theories on the enclosure's symbolism: inclusion and exclusion, the relationship between culture and nature or between people and their surroundings. The authors suggest that the monument drew on the memory of the past and may itself have been a metaphor for time. Deposits reveal a wide range of use including subsistence, eating, drinking, perhaps feasting, alliance, exchange, death and expression of gender roles. The later history of the enclosure, in the later Neolithic and Early Bronze Age, is also considered.